The Child as a Surrogate for Diagnosis of Lupus in the Mother - Olufemi O. Adelowo; Kenneth A. Ohagwu; Ejiehi E. Aigbokhan; Richard O. Akintayo (Case Reports in Rheumatology)
Introduction. Neonatal lupus erythematosus (NLE) is an acquired disease of the newborn caused by transplacental transfer of maternal anti-Ro/SSA, anti-La/SSB, and infrequently anti-U1 RNP antibodies. Methodology. This is a case report of a male infant delivered via Caesarean section at 36-week gestation following detection of fetal bradycardia during routine antenatal clinic visit. Results. The mother was seropositive for antinuclear antibody (ANA) and anti-Ro/SSA and had elevated erythrocyte sedimentation rate. The baby was positive for ANA, extractable nuclear antigen (ENA), and anti-Ro/SSA. Pediatric echocardiography was abnormal and electrocardiography confirmed complete heart block.